4-(4-(2-Bromoethyl)phenoxy)-2,3,5,6-tetrafluoropyridine - Tiffany H. Li; Lucas C. Messer; Nathan J. Weeks; Timothy J. Fuhrer; Scott T. Iacono (Molbank, 2023)
The title compound was synthesized in near quantitative yields via initial nucleophilic aromatic substitution of pentafluoropyridine (PFP) with 4-(2-bromoethyl)phenol as a versatile precursor for ionic liquids (ILs). The purity and structure were determined using 1H, 13C, and 19F NMR and GC-EIMS.